2022
DOI: 10.48550/arxiv.2207.02214
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutrino Fast Flavor Instability in three dimensions for a Neutron Star Merger

Abstract: The flavor evolution of neutrinos in core collapse supernovae and neutron star mergers is a critically important unsolved problem in astrophysics. Following the electron flavor evolution of the neutrino system is essential for calculating the thermodynamics of compact objects as well as the chemical elements they produce. Accurately accounting for flavor transformation in these environments is challenging for a number of reasons, including the large number of neutrinos involved, the small spatial scale of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…The Matter-Neutrino Resonance (MNR) occurs when the matter potential is equal to the neutrino self-interaction potential, and can impact the luminosity of ν e and νe within a few radii of the post-merger remnant [72,73]. The flast-flavor instability (FFI), on the other hand, is due solely to the neutrino self-potential, and seems to occur in regions where the sign of the net lepton flux (number flux of ν e minus number flux of νe ) changes for different directions of propagation of the neutrinos [74][75][76]. The FFI occurs on very short timescales (∼ns, i.e.…”
Section: Quantum Kinetics and Neutrino Oscillationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Matter-Neutrino Resonance (MNR) occurs when the matter potential is equal to the neutrino self-interaction potential, and can impact the luminosity of ν e and νe within a few radii of the post-merger remnant [72,73]. The flast-flavor instability (FFI), on the other hand, is due solely to the neutrino self-potential, and seems to occur in regions where the sign of the net lepton flux (number flux of ν e minus number flux of νe ) changes for different directions of propagation of the neutrinos [74][75][76]. The FFI occurs on very short timescales (∼ns, i.e.…”
Section: Quantum Kinetics and Neutrino Oscillationsmentioning
confidence: 99%
“…The FFI occurs on very short timescales (∼ns, i.e. cm length scales), and is likely active in many regions close to the post-merger remnant [76]. How much flavor transformation occurs as a result of the FFI remains uncertain, but recent studies using simplified prescription for where the FFI occurs and how much flavor transformation happens as a result have shown that it could plausibly lead to significant changes in the composition of matter outflows [77,78].…”
Section: Quantum Kinetics and Neutrino Oscillationsmentioning
confidence: 99%
“…For the fast mode, it converts neutrino flavors in a much shorter length scale ∼ (G F n ν ) −1 ∼ O(1) cm with G F the Fermi constant and n ν the neutrino number density. Studies have shown that fast instabilities generally exist in certain regions near or even inside the neutrinosphere in CCSNe modeled by multi-dimensional simulations [37][38][39][40][41][42][43], and are even more ubiquitously present in the postmerger environments of BNSMs [44][45][46][47][48][49][50][51]. The potential importance and the associated very short length scale of fast mode catalyzes recent surges of local dynamical simulations in tiny boxes [29,[51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…The matter-neutrino resonance (MNR) occurs when the matter potential is equal to the neutrino self-interaction potential, and can impact the luminosity of m e and m e within a few radii of the post-merger remnant (Caballero et al 2014;Zhu et al 2016). The flast-flavor instability (FFI), on the other hand, is due solely to the neutrino self-potential, and seems to occur in regions where the sign of the net lepton flux (number flux of m e minus number flux of m e ) changes between different directions of propagation of the neutrinos (Banerjee et al 2011;Wu et al 2017;Grohs et al 2022). The FFI occurs on very short timescales ( $ ns, i.e., cm length scales), and is likely active in many regions close to the post-merger remnant (Grohs et al 2022).…”
Section: Quantum Kinetics and Neutrino Oscillationsmentioning
confidence: 99%
“…The flast-flavor instability (FFI), on the other hand, is due solely to the neutrino self-potential, and seems to occur in regions where the sign of the net lepton flux (number flux of m e minus number flux of m e ) changes between different directions of propagation of the neutrinos (Banerjee et al 2011;Wu et al 2017;Grohs et al 2022). The FFI occurs on very short timescales ( $ ns, i.e., cm length scales), and is likely active in many regions close to the post-merger remnant (Grohs et al 2022). How much flavor transformation occurs as a result of the FFI remains uncertain, but recent studies using simplified prescriptions for where the FFI occurs and how much flavor transformation happens as a result have shown that it could plausibly lead to significant changes in the composition of matter outflows (Li and Siegel 2021;Fernández et al 2022).…”
Section: Quantum Kinetics and Neutrino Oscillationsmentioning
confidence: 99%